Analisa Alih Suplai Pertalite Menggunakan Mobil Tangki Di Pulau Bintan Kepri - Putri, Virgy Andyka (Ridwan Institute, 2021)
The purpose of this research was to analyze the transfer of pertalite supply using tank cars in Bintan Island Kepri Terminal X is one of the largest fuel terminals in Indonesia and is relied on to be a national oil stockpile reserve and has a very strategic role to provide fuel for the people of Aceh, North Sumatra, Riau, Riau Islands, Jambi, and surrounding areas. In February and March, there was a shortage of Pertalite products in Bintan Island because fuel supply using tangkers from Terminal X to Terminal Z was constrained by queues at Terminal X docks so that supplies had to be diverted to meet the needs of Pertalite products at Bintan gas stations. This prompted the author to analyze the transfer of Pertalite products from Terminal Z to Terminal X using cars for pertalite fuel distribution directly to gas stations in Bintan Kepri Island compared to the old pattern of from Terminal X to Terminal Z by boat and then using tank cars to gas stations in Bintan. Based on the results of the 2018 data analysis on distribution patterns, costs, losses, and quality, it can be concluded that the pattern of distribution from Terminal X to gas stations in Bintan will reduce the cost of transportation payments by Rp 92,175,460 in a year. In addition, it can also reduce losses by 35,671liters in a year.